ANALISIS DAMPAK PEMBANGUNAN PARIWISATA TERHADAP PENGEMBANGAN USAHA PARIWISATA DI KOTA PALU - Satrianingsih, Dian (Katalogis, 2015)
This research aims to (1) determine the role of local government, especially as regulator in tourism sector (Tourism Agency of Palu city), (2) determine the impact of tourism development to tourim business expansion in the city of Palu. This research is categories as descriptive qualitative. The findings show that (1) the government's role as regulator can be segregated into several roles, such as, fostering, coordinating, evaluating and monitoring all business activities in tourism sector in Palu(hotel, restaurant/cafe and travel and society in general). The role of local government in developing tourism sector in Palu has not been optimalised compare to the role of enterpreneur in tourism sector (2) The impact of tourism development can be seen as follow: the number of hotels as well as restaurant and cafe in Palu have been increased. In addition, the number of foreign and local tourists arrival has positive trend. Job opportunities in other sctors have also increased. Similarly, the economic improvement in the sector of commerce, hotels and restaurants have also positive trend especially in the issue ofÂ local tax. Furthermore,Â qualified festival and the annual tourism event, known as the Palu Bay Festival,can support the tourism and cultural sector of Palu City.